TANTANGAN GURU BAHASA ARAB MADRASAH ALIYAH DALAM PERSPEKTIF KOMPETENSI PEDAGOGIK DAN PROFESIONAL - Maman Abdurrahman; A. Suherman; Masor Masor; Asep M. Irfan Fadhlillah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2015)
Pedagogic & professional competence at the teacher is needed in the teaching & learning Arabic. Therefore it is needed a good preparation to support bath at competences in the teaching & learning Arabic. objectives of this study is to describe the important role of pedagogic and professional competence of Arabic teachers in Bandung, and their efforts to enhance both competences. The method used in this research is Naturalist Inquiry, by using Pedoman Penilaian Kinerja Guru Kemendiknas tahun 2010 for forty five Arabic teachers in Bandung. The result of the study showed that the degree of professional & pedagogic competence of Arabic teachers are normal (C). A caused by the linearity of their education. To be a Muallim Najih fi al-lughah Al-Arabiyah it needed a good professional and pedagogic competence.DOI: 10.15408/a.v2i1.1513